MEK inhibitors for the treatment of immunotherapy-resistant, AGK-BRAF fusion advanced acral melanoma: a case report and literature review - Yanling Zhang; Xifeng Zhang; Weikang Shao; Ji Gao; Mei Xiang; Yan Wang; Mengmeng Liu; Weizhen Zhang; Xianbin Liang (Journal of Cancer Research and Clinical Oncology)
Abstract Purpose Acral melanoma (AM), a rare and aggressive melanoma subtype with poor prognosis, presents unique challenges in treatment due to its distinct molecular and immune characteristics. This case report describes a patient with AM harboring an AGK-BRAF fusion mutation, aiming to explore potential mechanisms of resistance to current treatment modalities. Methods We analyzed tumor tissue samples from the primary and metastatic lesions of the patient using next-generation sequencing (NGS) for genomic profiling and multiplex immunohistochemistry (mIHC) to assess the immune microenvironment. The patient underwent multiple lines of treatment, including immunotherapy, chemotherapy, and targeted therapy, with their clinical outcomes documented and evaluated. Results The AGK-BRAF fusion mutation and its reciprocal BRAF-AGK rearrangement were identified in both primary and metastatic tumors. Immune profiling revealed abundant CD8 + T cells, PD-L1 + cells, and CD68 + macrophages localized predominantly in the tumor interstitial region, potentially explaining the poor response to immunotherapy. Despite initial disease stabilization with trametinib and lenvatinib, rapid progression occurred, highlighting tumor heterogeneity and limited efficacy of combined therapies. Conclusion This case underscores the need for personalized approaches in treating AM, especially those with rare molecular alterations like AGK-BRAF fusion. Insights from genomic and immune profiling may inform future therapeutic strategies to overcome resistance and improve outcomes in this challenging melanoma subtype.